Rib myelolipoma: a case report - André Amate Neto; Felipe Ramos Camargo Preto; Amanda Tollini de Moraes; Sarah Lopes Salomão; Thiago Barreto Frederigue; Mariane Nunes de Nadai; Marcel Koenigkam Santos; Tales Rubens de Nadai (Journal of Medical Case Reports, 2024)
Abstract Background Myelolipoma is an uncommon benign tumor composed of mature adipose tissue and hematopoietic elements. These tumors generally affect the adrenal glands, with anomalous presentations being rare and with few cases described in the literature. Most myelolipomas are asymptomatic and discovered incidentally, either through imaging tests or at autopsies. However, depending on the location and size of the lesion, myelolipomas can cause symptoms of mass effect. This article aims to report a very rare presentation of a symptomatic primary myelolipoma affecting the ribs. Case presentation A 21-year-old white female patient presented with a complaint of burning chest pain over 3 months, with gradual worsening in intensity, accompanied by a progressively growing bulge in the right thoracic wall. The patient underwent thoracotomy of the fifth and sixth ribs with complete excision of the lesion with a safety margin. Thoracic wall reconstruction was performed using a polypropylene mesh. The patient had a good postoperative course and was discharged on postoperative day 3. Histopathological examination revealed a histological image consistent with myelolipoma. Conclusions This report underscores the importance of considering a myelolipoma diagnosis for tumor masses in the ribs.